Peran Gaya Kepemimpinan terhadap Perilaku Kerja Pegawai Dukcapil Kabupaten Magelang - Jihan Fasabilla; Dinda Adiya Kirani; Defi Mayasaroh; Tivany Aulia Rahman; Aisya Dani Rosyada (Universitas Palangka Raya, 2026)
This study was conducted to examine, from an organizational behavior perspective, how leadership styles influence employee work behavior at the Population and Civil Registration Service (Dukcapil) of Magelang Regency. This study utilized various reference sources, including books, scientific journals, and previous research on leadership, organizational behavior, and employee work behavior. The results showed that certain leadership styles have a significant impact on employee work behavior, particularly in terms of improving discipline, motivation, responsibility, and the quality of public services. Transformational, democratic, and authentic leadership styles are considered more effective because they can create a good work environment, build trust, and encourage positive behaviors such as cooperation and initiative. Conversely, ineffective leadership can lead to low work motivation, decreased organizational commitment, and decreased quality of public services. Furthermore, this study shows that organizational systems are not the only factor influencing the success of public services; leaders also have the necessary expertise to direct and change employee work behavior. Therefore, a flexible and engaging leadership style is an important component in improving the quality of public services at Dukcapil of Magelang Regency.